The influence of Si/Al ratio on sulfate durability of metakaolin-based geopolymer. (30th December 2020) - Chen, Shikun; Zhang, Yajun; Yan, Dongming; Jin, Jiangchuxiong; Tian, Ye; Liu, Yi; Qian, Xiaoqian; Peng, Yu; Fujitsu, Satoru
Highlights: A strong coupling effect is found between Si/Al ratio and the sulfate type. The ion exchange process is found be dominated by different ions in sodium and magnesium sulfate solutions. The influence of Si/Al ratio is notable in magnesium sulfate solution but negligible in sodium sulfate solution. Abstract: The durability of geopolymers in sulfate is essential to their application in harsh environments. In this paper, the influence of Si/Al ratio, one of the major composition parameters of metakaolin-based geopolymer (MKG), on its durability in both sodium and magnesium sulfate solutions was investigated in detail. The results indicate there is a strong coupling effect appears between Si/Al ratio and the sulfate type. The ion exchange process of MKG with different Si/Al ratios is significantly influenced by the cation of sulfate. The exchange of OH − and SO4 2− dominates the ion exchange process in sodium sulfate solution while the exchange of Na + and Mg 2+ dominates in magnesium sulfate solution. In addition, the variation of strength, chemical structure, micromorphology in two sulfate environments is also closely dependent on Si/Al ratio. The Si/Al ratio shows notable influence on micromorphology and strength in magnesium sulfate solution while there is negligible influence of Si/Al ratio in sodium sulfate solution.